Peran Academic Self-Efficacy sebagai Variabel Mediator dalam Hubungan antara Growth Mindset dan Academic Resilience pada Mahasiswa - Putriadi, Harvi Wahyu; Ni’matuzahroh, Ni’matuzahroh (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
University students face increasing academic demands that may affect both their psychological well-being and academic success. One essential capacity that enables students to cope with such demands is academic resilience. This study aims to examine the relationship between growth mindset and academic resilience among university students and to investigate the mediating role of academic self-efficacy. A quantitative correlational design was employed, involving undergraduate students as research participants. Data were collected using self-report questionnaires measuring growth mindset, academic self-efficacy, and academic resilience, and were analyzed using regression and path analysis. The findings indicate that growth mindset is positively associated with academic self-efficacy, and academic self-efficacy is positively related to academic resilience. Furthermore, academic self-efficacy was found to significantly mediate the relationship between growth mindset and academic resilience. These results suggest that students’ academic resilience is shaped not only by their beliefs about the malleability of abilities but also by their confidence in managing academic challenges. This study highlights the importance of fostering growth mindset and academic self-efficacy to strengthen students’ academic resilience in higher education contexts.